Administration of the Student Support System in the Digital Age of Schools in the Hang Dong Educational Quality Development Network Group 2 under the Chiang Mai Primary Educational Service Area Office 4 - Suwannamangkorn, Nutthakan; Suttasiri, Surasak; Wangcham, Sangwan; Boonmaphi, Tasnee (MCU Haripunchai Review, 2025)
The purpose of this study was to study and find guidelines to develop the Administration of the Student Support System in the Digital Age of Schools in the Hang Dong Educational Quality Development Network Group 2 under the Chiang Mai Primary Educational Service Area Office 4. The sample was 107 school administrators and teachers in the academic year 2024. And 6 qualified persons in interviews, chosen by the specific method. Tools included questionnaires and interviews, the data was analyzed by mean, standard, deviations, and context analysis. The research results found that: 1) The Administration of the Student Support System in the Digital Age of Schools in the Hang Dong Educational Quality Development Network Group 2 under the Chiang Mai Primary Educational Service Area Office 4, in the overall, was at a high level. When considering on a side-by-side basis, it was found that it was at a high level in all aspects, in descending order of averages, namely supporting and developing students, knowing students individually, referring students, preventing and solving student problems, and screening students, respectively. 2) Guidelines for the development of the Administration of the Student Support System in the Digital Age of Schools in the Hang Dong Educational Quality Development Network Group 2 under the Chiang Mai Primary Educational Service Area Office 4 were that the schools need to utilizing cloud computing in student record management. Key recommendations include: (1) establishing clear policies with data security measures and staff training; (2) using cloud computing for student screening to enhance efficiency, accuracy, and real-time updates with adequate budget support; (3) using cloud computing in parent-teacher meetings for systematic data collection; (4) employing Google Drive, Forms, and Sheets for structured data storage and analysis; and (5) leveraging social networks to support and monitor student assistance. These measures enhance efficiency, security and accessibility in education management.